Avaliação da Fertilidade na Raça Caracu - Luiz Gustavo Cavalca (2022)
Objectives: The objectives were: Chapter 1) To compare the different methods used to assess permanence ability (HP), calculate its heritability, to know if it is a good trait to be selected in caracu cattle. Cap.2) Evaluate the probability of offspring repetition within 14 months (PRC14), calculate its heritability and repeatability. Compare with permanence skill to recommend the best trait to select. Material and methods: The reproductive information of 17568 births from 5555 sows, whose births took place between 2003 and 2020, belonging to the Caracu herd of Fazenda Arinos, located in the municipality of Diamantino, state of Mato Grosso, were used. In addition, another 3558 animals that make up the pedigree of these animals and that will be included in the kinship matrix used in the analysis were included in the analysis. The statistical package SAS (1990) will be used for the formation of files, consistency and descriptive analysis of the data. Permanence ability was evaluated in two ways, the usual HP6/3, where every animal that presented the first offspring in the database up to 40 months of age had a valid phenotype, and those with three offspring registered up to 76 months of age have the manifestation of “success” in the permanence ability characteristic and those who did not have three offspring manifest “failure” in the permanence ability characteristic. In the second form (HP4/2), the number of pups drops to two and the time for permanence drops to 52 months, from having their first calving to 26 months. The other characteristic considered was the probability of calving repetition in up to 14 months (PRC14), a calving interval considered maximum for a cow to repeat calving in a herd management system with a three-month breeding season. In this case, all calved cows manifest a phenotype for each of their offspring, being “success” if the calving interval is less than 14 months and “failure” if this interval is greater than 14 months or this is the last calving interval. their offspring, and every possibility of repeating a birth within 14 months generates a data, whether positive (repeat birth) or negative (not repeated birth). The model used in the analysis of permanence ability included the fixed effects of the group of contemporaries (composed of year and time of birth of the sow), and the linear effect of differences in age of females nested within the group of contemporaries. In addition, direct additive and residual random effects were included, each with its specific variance component. For trait PRC14, we used the fixed effects of contemporary group (consisting of year and time of birth and sex of the calf), the effect of cow age at calving nested within sex, the linear effect of nested calving date differences within the group of contemporaries. there was also the random effect of the cow's permanent environment, since a repeatability model was used for this characteristic. A threshold model was used, in which the hidden underlying scale follows normal distribution with the linear model above that, together with the threshold of manifestation of the characteristic, defines the probability of manifestation of the phenotypes in the observed scale (remained or not, repeated breeds or no). The variance components were estimated by Bayesian inference using Monte Carlo methods based on Markov chains implemented in the thrgibbs1F90 software (Mizstal et al., 2002). Sufficient length chains were used to achieve an effective sample size equal to or greater than 100 independent samples. Analysis Template for HP Yij=C+Gci+ai+eij Analysis model for PRC14 Yij=C+Gci+bi(Ibij-IBi)+f(IVPi)+ai+pi+eij Yij=0nor 1, if Yij<0 or Yij>0 Results: Both traits have low heritability. Conclusions: Even though they are two distinct traits, which presented low and similar heritability, they should be included in selection programs, due to their great importance in the productivity and profitability of the herd. Keywords: Caracu. Stayability. Fertility.